Endolumenal Vacuum Therapy and Fistulojejunostomy in the Management of Sleeve Gastrectomy Staple Line Leaks - Kyle Szymanski; Estrellita Ontiveros; James S. Burdick; Daniel Davis; Steven G. Leeds (Case Reports in Surgery)
Laparoscopic sleeve gastrectomy (LSG) is the most common bariatric surgery performed for morbid obesity. Leaks of the vertical staple line can occur in up to 7% of cases and are difficult to manage. Endolumenal vacuum (EVAC) therapy and fistulojejunostomy (FJ) have separate documented uses to heal these complicated leaks. We aim to show the benefit of using EVAC with FJ in the treatment of LSG staple line leaks. The patient presented with an LSG chronic leak. EVAC therapy was initiated but failed to close the fistula after 101 days. EVAC therapy was abandoned, and FJ was performed to resolve the leak. Postoperatively, no leak was encountered requiring any additional procedures. Based on our findings, we conclude that EVAC therapy facilitates in resolving leaks that restore gastrointestinal continuity and maintain source control. It promotes healing and causes reperfusion of ischemic tissue and fistula cavity debridement.